Plasmonic metaresonances: harnessing nonlocal effects for prospective biomedical applications. (24th May 2019) - Hapuarachchi, Harini; Gunapala, Sarath D; Premaratne, Malin
Abstract: Metal nanoparticles (MNPs) possess optical concentration capabilities that can amplify and localize electromagnetic fields into nanometer length scales. The near-fields of MNPs can be used to tailor optical response of luminescent semiconductor quantum dots (QDs), resulting in fascinating optical phenomena. Plasmonic metaresonances (PMRs) form a class of such optical events gaining increasing popularity due to their promising prospects in sensing and switching applications. Unlike the basic excitonic and plasmonic resonances in MNP-QD nanohybrids, PMRs occur in the space/time domain. A nanohybrid experiences PMR when system parameters such as QD dipole moment, MNP-QD centre separation or submerging medium permittivity reach critical values, resulting in the plasmonically induced time delay of the effective Rabi frequency experienced by the QD asymptotically tending to infinity. Theoretical analyses of PMRs available in the literature utilize the local response approximation (LRA) which does not account for the nonlocal effects of the MNP, and neglect the MNP dependence of the QD decay and dephasing rates which hinder their applicability to QDs in the close vicinity of small MNPs. Here, we address these limitations using an approach based on the generalized nonlocal optical response (GNOR) theory which has proven to yield successful theoretical explanations of experimentally observed plasmonic phenomena. Our results indicate that, omission of the MNP nonlocal response and the associated decay/dephasing rate modifications of the QD tend to raise implications such as significant over-estimation of the QD dipole moment required to achieve PMR, under-estimation of the critical centre separation and prediction of significantly lower near-PMR QD absorption rates, in comparison to the improved GNOR based predictions. In light of our observations, we finally suggest two prospective applications of PMR based nanoswitches, namely, aptamer based in vitro cancer screening and thermoresponsive polymer based temperature sensing. To demonstrate the latter application, we develop and utilize a proof of concept (two dimensional) skin tumor model homogeneously populated by MNP-QD nanohybrids. Our simulations reveal a novel near-PMR physical phenomenon observable under perpendicular illumination, which we like to call the margin pattern reversal, where the spatial absorption pattern reverses when the near-PMR QDs switch from the bright to dark state.